Remote ischaemic preconditioning reduces myocardial injury in patients undergoing cardiac surgery with cold-blood cardioplegia: a randomised controlled trial. Issue 19 (8th June 2009) - Venugopal, V; Hausenloy, D J; Ludman, A; Di Salvo, C; Kolvekar, S; Yap, J; Lawrence, D; Bognolo, J; Yellon, D M
Abstract : Background: Remote ischaemic preconditioning (RIPC) induced by brief ischaemia and reperfusion of the arm reduces myocardial injury in coronary artery bypass (CABG) surgery patients receiving predominantly cross-clamp fibrillation for myocardial protection. However, cold-blood cardioplegia is the more commonly used method world wide. Objective: To assess whether RIPC is cardioprotective in CABG patients receiving cold-blood cardioplegia. Design: Single-centre, single-blinded, randomised controlled trial. Setting: Tertiary referral hospital in London. Patients: Adults patients (18–80 years) undergoing elective CABG surgery with or without concomitant aortic valve surgery with cold-blood cardioplegia. Patients with diabetes, renal failure (serum creatinine >130 mmol/l), hepatic or pulmonary disease, unstable angina or myocardial infarction within the past 4 weeks were excluded. Interventions: Patients were randomised to receive either RIPC (n = 23) or control (n = 22) after anaesthesia. RIPC comprised three 5 min cycles of right forearm ischaemia, induced by inflating a blood pressure cuff on the upper arm to 200 mm Hg, with an intervening 5 min reperfusion. The control group had a deflated cuff placed on the upper arm for 30 min. Main outcome measures: Serum troponin T was measured preoperatively and at 6, 12, 24, 48 and 72 h after surgery and the area under the curve (AUC at 72 h) calculated. Results: RIPC reduced absolute serum troponin T release by 42.4% (mean (SD) AUC at 72 h: 31.53 (24.04) μg/l.72 h in controls vs 18.16 (6.67) μg/l.72 h in RIPC; 95% CI 2.4 to 24.3; p = 0.019). Conclusions: Remote ischaemic preconditioning induced by brief ischaemia and reperfusion of the arm reduces myocardial injury in CABG surgery patients undergoing cold-blood cardioplegia, making this non-invasive cardioprotective technique widely applicable clinically. Trial registration number: NCT00397163.